The Kinetic Study On The Effects Of Mixed Aqueous-Organic Solvents On The Rate Of O- And N- Cyclisation Of N-(4 '-Nitrophenyl)Phthalamic Acid - Ariffin, Azhar; Khan, M.N.; Ahmad, W.H.W. (2007)
The pseudo-first-order rate constants (k(obs)) for the intramolecular carboxylic group-assisted cleavage of N-(4'-nitrophenyl)phthalamic acid (1) show nonlinear decrease of similar to 17-fold and similar to 117-fold with the increase in the respective contents of CH3CN (10-80% v/v) and 1,4-dioxan (9.5-79.4% v/v) in mixed aqueous solvents. The fraction of N-cyclization of 1 leading to the formation of N-(4'-nitrophenyl)phthalimide, 2, remains almost zero at <= 40% v/v CH3CN while it increases from 0.06 to 0.49 with increase in CH3CN content (50-80% v/v) at 1.0 x 10(-3) M HCl. However, the observed data reveal an almost absence of N-cyclization within 1,4-dioxan content range 10-80% v/v.